Catalpol Inhibits Macrophage Polarization and Prevents Postmenopausal Atherosclerosis Through Regulating Estrogen Receptor Alpha - Chen, Qi; Qi, Xu; Zhang, Weiwei; Zhang, Yuhan; Bi, Yunhui; Meng, Qinghai; Bian, Huimin; Li, Yu (Frontiers in Pharmacology, 2021)
Lacking estrogen increases the risk of atherosclerosis (AS) in postmenopausal women. Inflammation plays a vital role in the pathological process of AS, and macrophages are closely related to inflammation. Catalpol is an iridoid glucoside extracted from the fresh roots of the traditional Chinese herb Rehmanniae radix preparata. In this study, we aimed to evaluate the effects of catalpol on macrophage polarization and postmenopausal AS. In addition, we investigated whether the mechanism of catalpol was dependent on regulating the expression of estrogen receptors (ERs). In vitro, lipopolysaccharides (LPS) and interferon-γ (IFN-γ) were applied to induce M1 macrophage polarization. In vivo, the ApoE-/- mice were fed with a high-fat diet to induce AS, and ovariectomy was operated to mimic the estrogen cessation. We demonstrated catalpol inhibited M1 macrophage polarization induced by LPS and INF-γ, and eliminated lipid accumulation in postmenopausal AS mice. Catalpol not only suppressed the inflammatory response but also reduced the level of oxidative stress. Then, ERs (ERα and ERβ) inhibitors and ERα siRNA were also applied in confirming that the protective effect of catalpol was mediated by ERα, rather than ERβ. In conclusion, catalpol significantly inhibited macrophage polarization and prevented postmenopausal AS by increasing ERα expression.